Determinants of membership in Farmers’ Organisations in Tanzania - Miyanda, Webster; Shungu, Hamidu; Ngaruko, Deus (IJRDO - Journal of Business Management, 2016)
This study aims at identifying factors that determine Farmers’ Organisations membership in Tanzania. The study was conducted in Mbeya and Kilimanjaro regions. It is based on Farmer Organisations (FOs) members and expert informants interviews in which both qualitative and quantitative cross sectional data were collected. The method used was a mixed one for data collection in which interviews; questionnaire, FGDs and case studies were employed. Descriptive analysis was used to identify factors influencing membership in FOs. The results reveal that individual characteristics, FOs internal and external factors are significant in influencing FOs membership. The study recommends that FOs facilitators should identify strategies that encourage the youth and women in membership. It argues that member identification and recognition is vital in FOs sustainability. The research further recommends that FOs facilitators, and leaders facilitate and adhere to member self-selection strategies and value quality instead of quantity in membership in order to increase membership in FOs.